Processing of dairy products and research on the composition of probiotic fermented drinks based on acid whey (Texas Journal of Engineering and Technology, 2023)
Whey is a very useful product. The amount of whey created depends on the amount of cheese production, as well as the fertility depending on the type of milk, and about 9 L of whey is obtained for every 1 kg of cheese produced. The main problem lies in the high organic load, mainly due to the high content of lactose, but also the appearance of proteins that are difficult to biodegrade. More precisely, the chemical oxygen demand (COD) of cheese whey can vary from 50,000 to 80,000 mg / l, while the biochemical oxygen demand (BOD) ranges from 40,000 to 60,000 mg / l . The rapid consumption of oxygen in the soil as a result of the breakdown of proteins and sugars present in whey, in accordance with the large volume generated, presents the problem of large amounts of elimination. In this context, the production of lactic acid, ethanol, microbial lipids, microbial biomass, single-cell protein, Poly-hydroxyalkanoates, enzymes and endo-polysaccharides